Pelatihan Editing Video Guna Peningkatan Kreativitas Karang Taruna Pada Desa Mangga Dua - Dito Putro Utomo; Bister Purba; Fince Tinus Waruwu (Jurnal Mitra Pengabdian Farmasi, 2022)
In the current era of technological progress, many institutions have used and taken advantage of these technological advances. Not only large-scale institutions or organizations, small-scale institutions or organizations have also taken advantage of the role of this technology. Likewise with Mangga Dua Village which has taken advantage of these technological advances. Mangga Dua Village collaborates with Karang Taruna to assist in the process of disseminating information conveyed to communities outside Mangga Dua Village by utilizing the role of technology. In Mangga Dua Village, the role of Karang Taruna is to help advance and develop Mangga Dua Village. One of the main roles of Karang Taruna is to assist in the use of technology for the process of product marketing activities produced by the community in Mangga Dua Village. The promotion process for Mangga Dua Village products and also the Mangga Dua Village profile will later be carried out in the form of videos to make it easier to see the message conveyed. The lack of knowledge or expertise of Karang Taruna members is because there is still no training or assistance in the process of creating video content. The video editing process has now been helped a lot with free applications that can be accessed and used by anyone. Video editing training conducted by the Budi Darma University dedication team to members of the Mangga Dua Village Youth Organization is useful for assistance in video editing and also aims to increase creativity for Karang Taruna members.